Pengelolaan Guru Pendidikan Agama dalam Konteks Desentralisasi Pendidikan - Hayadin -- (Jurnal Pendidikan dan Kebudayaan, 2012)
The objective of this study is to describe the process of managing religious education teachers in the era of decentralization of education in Palangkaraya City, Central Kalimantan Province. This study was a case study–qualitative in nature which was conducted in 2010. The data was collected directly in Palangkaraya City using primary and secondary data sources, which is information and document from office of the Ministry of Religious Affairs, education office, and local personnel board of Palangkaraya City. To collect the data, the researcher used interview and document study with interview sheets and checklist. The data was verified through triangulation to some resource persons in relation to the one research problem in order to ensure the validity and reliability. The findings showed that: 1) recruitment of religious education teachers was also conducted by Palangkaraya local administration in order to meet the requirement of religious teachers in the city because the number of teachers appointed by the central government (cq, Ministry of Religious Affairs) is so small; 2) In the process of career development and welfare, religious education teacher is treated with the same respect as other teachers; 3) Socialpolitical conditions and the clarity of Regional Personnel Board Regulation concerning management of local personnel are other factors contributing to the management of religious education teachers in Palangkaraya City. ABSTRAK Penelitian ini bertujuan untuk menjelaskan proses pengelolaan guru pendidikan agama di era desentralisasi pendidikan di Kota Palangkaraya Provinsi Kalimantan Tengah. Penelitian ini merupakan studi kasus yang bersifat kualitatif yang dilakukan pada tahun 2010. Pengumpulan data dilakukan secara langsung di Kota Palangkaraya, dengan sumber data primer dan sekunder yang berasal dari data dan dokumen yang diperoleh di kantor Kementerian Agama, Dinas Pendidikan dan Badan Kepegawaian Daerah Kota Palangkaraya. Untuk mengumpulkan data tersebut, peneliti menggunakan metode wawancara, dan studi dokumen, dengan instrumen pedoman wawancara dan cheklist kelengkapan dokumen. Proses verifikasi data melalui triangulasi kepada beberapa narasumber terhadap satu isu yang diteliti dilakukan untuk menjamin keabsahan dan kebenaran data yang diambil. Hasil penelitian menunjukkan bahwa: 1) rekruitmen tenaga pendidik guru pendidikan agama di era desentralisasi turut dilakukan oleh pemerintah daerah Kota Palangkaraya dalam rangka untuk memenuhi kebutuhan guru agama di daerah tersebut. Hal tersebut karena jumlah tenaga kependidikan yang diangkat oleh pemerintah pusat (c.q, Kementerian Agama RI) masih sangat kurang; 2) dalam proses pembinaan karir dan kesejahteraan, tenaga pendidik guru pendidikan agama mendapatkan perlakuan yang sama dengan guru lainnya; 3) kondisi sosial politik dan kejelasan Peraturan Badan Kepegawaian Daerah tentang Manajemen Pegawai Daerah merupakansalah satu faktor pendukung dari pengelolaan guru pendidikan agama di Kota Palangkaraya.